THE IMPACT OF STORYTELLING IN THE CLASSROOM - Qadirova Dilnura (TADQIQOTLAR.UZ, 2023)
Abstraction. Storytelling is about the art of reciting a tale from memory rather than reading, it is regarded to be one of the oldest of all art forms, dating back to prehistoric times. Majority of EFL teachers find it spellbinding resource in teaching. Storytelling is the original form of teaching and has the potential of promoting emotional intelligence and help the child gain insight into human behavior. Moreover, It can provide a motivating and low anxiety context for language learning. In this article, I am also going to clarify some storytelling tips which are meant to be of help to the teacher–as storyteller as s/he prepares for a storytelling "performance" for students.